Long-Term Data Reveal the Associations of the Egg Quality With Abiotic Factors and Female Traits in the Baltic Herring Under Variable Environmental Conditions - Rajasilta, Marjut; Mäkinen, Katja; Ruuskanen, Suvi; Hänninen, Jari; Laine, Päivi (Frontiers in Marine Science, 2021)
In fish, the lipid resources of the female form a link between the environment and progeny, contributing to the contents of the egg yolk. Variation of the environmental conditions is therefore expected to affect the egg quality via maternal pathways, reflecting the female’s response to the environmental factors before spawning. We investigated the content of lipids and thyroid hormones in the ovary and eggs of the Baltic herring during 1988–2019, when salinity of the Baltic Sea first declined and then stabilized to a lower level, and winters varied between severe and mild. The total lipid resources of spawning females decreased by 40–50% during the study, and the ovarian lipid concentration followed this trend resulting in a decrease of the lipid content of eggs. The concentration of thyroid hormones in the ovary suggested a hormonal response in females to salinity and winter temperature and was observable also in the content of thyroid hormones in the eggs. A change in the egg lipid content took place approximately around 1998 (SE ± 3 years) suggesting that in declining salinity, egg quality was associated with salinity and intrinsic factors in the female, i.e., fecundity and amount of lipids deposited into the ovary. However, during the period of stable salinity, egg quality was mainly limited by the female’s lipid resources. As also the body size of the females decreased over the years, it is suggested that small body size can be a key phenotypic trait to reduce the environmental impact on egg quality in variable environmental conditions.